Temperature regulates synaptic subcellular specificity mediated by inhibitory glutamate signaling. - Mengqing Wang; Daniel Witvliet; Mengting Wu; Lijun Kang; Zhiyong Shao (PLoS Genetics)
Environmental factors such as temperature affect neuronal activity and development. However, it remains unknown whether and how they affect synaptic subcellular specificity. Here, using the nematode Caenorhabditis elegans AIY interneurons as a model, we found that high cultivation temperature robustly induces defects in synaptic subcellular specificity through glutamatergic neurotransmission. Furthermore, we determined that the functional glutamate is mainly released by the ASH sensory neurons and sensed by two conserved inhibitory glutamate-gated chloride channels GLC-3 and GLC-4 in AIY. Our work not only presents a novel neurotransmission-dependent mechanism underlying the synaptic subcellular specificity, but also provides a potential mechanistic insight into high-temperature-induced neurological defects.